Ultrafast ppb-level triethylamine detection sensor based on self-assembled hierarchical structures of Ag/WO3 nanoflowers - Bi, Yubo; Cui, Zhancheng; Zhao, Yang; Gao, Wei; Bi, Mingshu (Journal of alloys and compounds, 2025)
The development of triethylamine (TEA) gas sensors exhibiting superior selectivity and rapid response is a significant and demanding subject. This study achieved the synthesis of three-dimensional WO3 nanoflower structures by a straightforward hydrothermal approach utilizing Na2WO4-2H2O and oxalic acid in HCl solution in a self-assembled way. The WO3 nanoflower hierarchical structure, composed of 2D nanosheets, can be distinctly recognized by characterization techniques such as SEM and TEM, facilitating gas molecule passage and optimizing the utilization of the sensing material. The WO3 sensor demonstrates an exceptionally rapid response time of 2 s and a remarkable response of 254 at 300 ℃ for 100 ppm TEA. Moreover, the material was further optimized by including the noble metal Ag into the WO3 nanoflowers. The test results indicate that the Ag/WO3-2 sample exhibits an exceptionally rapid response time of 1 s, a high response of 837 (Ra/Rg), remarkable selectivity, and enduring stability at 250 ℃ and 100 ppm TEA. Additionally, the sample displays a response rate of 1.84–100 ppb to TEA gas at a temperature of 250 ℃. Investigations are also conducted into how the TEA gas sensor performed in relation to relative humidity. This outstanding sensing capability is largely related to the unique hierarchical WO3 nanoflower structure and the loading of the noble metal Ag. The Ag/WO3 composite offers numerous gas adsorption sites and the catalytic properties of Ag, resulting in a significant enhancement in sensor performance. This study presents a novel and efficient approach for designing TEA sensors that have rapid response times and strong selectivity. •Unique WO3 nanoflower hierarchical structures consisting of self-assembled stacks of nanosheets were synthesized.•Ag-loaded floral WO3 nanocomposites showed ultrafast response to triethylamine (1 s).•WO3 nanomaterials enabled ppb-level triethylamine response.•The sensing enhancement mechanism of Ag was investigated.